2009
DOI: 10.1111/j.1751-7141.2009.00030.x
|View full text |Cite
|
Sign up to set email alerts
|

National Cholesterol Education Panel ΙΙΙ Guidelines Performance Role in Preventing Myocardial Infarction in a Large Cohort Without a History of Coronary Artery Disease: Korea Acute Myocardial Infarction Registry Study

Abstract: The Third Report of the Adult Treatment Panel National Cholesterol Education Program (NCEP-ATP III) guidelines are widely used for the primary prevention of a coronary event. These guidelines were developed using experimental data from studies that enrolled mostly Caucasian patients. The pathogenesis of atherosclerosis varies with ethnicity. Given these two circumstances, the authors sought to investigate the performance of the guidelines in a large Asian cohort. The Korea Acute Myocardial Infarction Registry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In 2009 and 2012, two Korean studies revealed that the NECP-ATP III guidelines (the most popular Western guidelines for the primary and secondary prevention of cardiovascular disease) were not completely suitable for the Korean population 23,24) . Additionally, several Japanese studies have reported the clinical significance of statin therapy for the primary and secondary prevention of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In 2009 and 2012, two Korean studies revealed that the NECP-ATP III guidelines (the most popular Western guidelines for the primary and secondary prevention of cardiovascular disease) were not completely suitable for the Korean population 23,24) . Additionally, several Japanese studies have reported the clinical significance of statin therapy for the primary and secondary prevention of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-day clinical outcome was worse in women than men both in STEMI and NSTEMI. In addition, Yoon et al [21] observed that the U.S. National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP) III recommendations [22], the most widely used guidelines for the primary prevention of coronary events, are less reliable in Koreans, particularly in women as compared with men.…”
Section: Risk Factors For Amimentioning
confidence: 99%
“…Yoon et al48 found that application of the NCEP-ATP III guidelines, which were mainly developed from Caucasian patients, to data from the Korea Acute Myocardial Infarction Registry (KAMIR) resulted in undertreatment. Around 69% of patients with an acute MI did not qualify for drug therapy when they were stratified according to the risk factors present and the 10-year CHD risk.…”
Section: Guidelines In Asian Versus Western Countriesmentioning
confidence: 99%